Diversity and phylogenetic position of the amphi-American lineages of the tapeworms of the genus Anthocephalum Linton, 1890 (Rhinebothriidea: Anthocephaliidae) - Sakai, Lilian F.; Marques, Fernando P.l.; Trevisan, Bruna (Zootaxa, 2025)
Among enduringly associated parasitic taxa, tapeworms (Platyhelminthes: Cestoda), particularly the family Anthocephaliidae Ruhnke, Caira & Cox, 2015, pose challenges to systematic history of the group. Within this family, the genus Anthocephalum Linton, 1890, remains insufficiently explored despite recent advancements. This study addresses the intricate taxonomy, phylogenetic relationships, diversity, and historical biogeography of tapeworms within the Anthocephaliidae, focusing on its type-genus Anthocephalum. To accomplish this objective, 15 specimens across various geographical regions including Alagoas and Pará in Brazil, Panama, and Senegal were selected for DNA extraction. For species of Anthocephalum, partial 18S and 28S rDNA sequences were amplified via PCR, purified, and sequenced using the ABI Big-Dye method. Three specimens of Alveobothrium grabatum Boudaya, Neifar & Euzet, 2018 were sequenced through Illumina technology. Phylogenetic analyses were conducted using IQTREE2 under two optimality criteria: Maximum Parsimony (MP) and Maximum Likelihood (ML). Biogeographic ancestral range estimations were performed using the R package BioGeoBEARS, incorporating multiple biogeographical models. Our phylogenetic analyses reaffirmed Anthocephaliidae’s monophyly. However, both the relationships with or within Anthocephaliidae require further investigation. One example within the family is the positioning of Alveobothrium Boudaya, Neifar & Euzet, 2018, which challenged Anthocephalum’s monophyly requiring taxonomic actions. Furthermore, when exploring new localities and/or new hosts for Anthocephalum, four independent lineages were identified, suggesting that Anthocephalum’s diversity remains underestimated especially in unexplored regions and hosts. About the biogeographic ancestral range estimation, the analysis suggested a Central Indo-Pacific origin for early Anthocephalum lineages, with subsequent colonization events shaping the current diversity. The preliminary biogeographical framework presented here underscores the importance of refining phylogenetic hypotheses and enhancing taxonomic understanding. As taxonomic actions taken, the four new lineages were formally described and the genus Alveobothrium was synonymized with Anthocephalum, for which we proposed an amended diagnosis. This revision brings the total number of valid species of Anthocephalum to 30. Therefore, we suggest that future research initiatives should prioritize time-calibrated analyses, multiple genetic loci, and broader taxonomic representation for a detailed exploration of systematic history of anthocephaliid’s.